HRH dimensions of community health workers: a case study of rural Afghanistan - Said Ahmad Maisam Najafizada; Ronald Labonté; Ivy Lynn Bourgeault (BMC, 2019)
Abstract Introduction There is ample evidence to indicate that community health workers (CHW) are valuable human resources for health in many countries across the globe, helping to fill the gap created by a chronic health workforce shortage. This shortage is not only in number but also in workforce distribution and skill mix. There remains a lack of evidence, however, concerning the size and distribution of CHWs and their relationship to the professionally regulated and recognized health workforce, such as physicians and nurses, and the unregulated and unrecognized health workforce, such as traditional birth attendants and traditional healers. This is particularly the case in low-income, under-resourced countries, such as Afghanistan. Method We conducted a descriptive qualitative analysis involving fieldwork in Afghanistan between 2013 and 2014. We undertook participant observation and in-depth interviews with community members, CHWs, health managers, and policymakers, in an attempt to add more depth to our knowledge of how CHWs function, or could function better, as a recognized health worker. Results We found that the number of CHWs has increased dramatically in recent years and that CHWs play a variety of roles, including work generally associated with professional providers, such as referral, education, and counseling. Although not a replacement for professional health providers, CHWs, in places where the number of and access to such providers is low, become the only option to meet basic health needs of the population. In places where professional providers are available, CHWs have the potential to extend the services to marginalized populations, provide community health services, and become a recognized member of the health provider team. A limitation of their role in health system strengthening is their lack of integration and a clear career path including into more recognized professional roles. Conclusion CHWs provide a critical human resources for health role in Afghanistan, but there are opportunities for improved integration with other providers which can increase their potential to improve service delivery.